A phenomenological inquiry on the devotees of the miraculous image of San Agustin De Tanza, Philippines - LORENZO ALVIN T. CAPIO; SUSANA R. REYES (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This paper aims to provide greater clarity between Church authorities and churchgoers by gaining profound insights into the lived experiences of one of the popular devotions in Cavite, Philippines.Method: This research uses a phenomenological method to describe, interpret, and reflect on the experiences of devotees who have visited the San Agustin shrine in search of signs that the miraculous image of San Agustin holds meaning for Catholic spirituality. Creswell (1998) suggests conducting in-depth interviews with six participants to achieve a multi-perspective understanding of a phenomenon. The current study followed this advice. The interviewees’ permission was also required to use their audio recordings and their raw experiences to analyse data.Findings: According to the results of this research, believers’ faith in the miraculous image of San Agustin de Tanza stems solely from their personal encounters with God. If you ask Pieris (2007), this is not a form of idolatry or animism; rather, it is cosmic religiosity.Implications/Novel Contribution: There is a need for a healthy and innovative relationship between churchgoers and church officials, and this study sheds light on some of the challenges the church faces today, like a growing number of churchgoers who are inactive in the church’s activities. This research can potentially improve communication between laypeople and religious leaders over time.